Effect of exogenous and endogenous ketones on respiratory exchange ratio and glucose metabolism in healthy subjects - Dörner, Rebecca; Hägele, Franziska A.; Müller, Manfred J.; Seidel, Ulrike; Rimbach, Gerald; Bosy-Westphal, Anja (American Journal of Physiology: Cell Physiology, 2024)
Our findings revealed that during isocaloric nutrition, additional exogenous ketone salts increased V̇o 2 and V̇co 2 while lowering the respiratory exchange ratio (RER). Ketone salts had no effect on postprandial glucose metabolism. This study examined the effect of exogenous ketone bodies (KB) on oxygen consumption (V̇o 2 ), carbon dioxide production (V̇co 2 ), and glucose metabolism. The data were compared with the effects of endogenous ketonemia during both, a ketogenic diet or fasting. Eight healthy individuals [24.1 ± 2.5 yr, body mass index (BMI) 24.3 ± 3.1 kg/m 2 ] participated in a crossover intervention study and were studied in a whole-room indirect calorimeter (WRIC) to assess macronutrient oxidation following four 24-h interventions: isocaloric controlled mixed diet (ISO), ISO supplemented with ketone salts (38.7 g of β-hydroxybutyrate/day, EXO), isocaloric ketogenic diet (KETO), and total fasting (FAST). A physical activity level of 1.65 was obtained. In addition to plasma KB, 24-h C-peptide and KB excretion rates in the urine and postprandial glucose and insulin levels were measured. Although 24-h KB excretion increased in response to KETO and FAST, there was a modest increase in response to EXO only ( P < 0.05). When compared with ISO, V̇o 2 significantly increased in KETO ( P < 0.01) and EXO ( P < 0.001), whereas there was no difference in FAST. V̇co 2 increased in EXO but decreased in KETO (both P < 0.01) and FAST ( P < 0.001), resulting in 24-h respiratory exchange ratios (RER) of 0.828 ± 0.024 (ISO) and 0.811 ± 0.024 (EXO) ( P < 0.05). In response to EXO there were no differences in basal and postprandial glucose and insulin levels, as well as in insulin sensitivity. When compared with ISO, EXO, and KETO, FAST increased homeostatic model assessment β-cell function (HOMA-B) (all P < 0.05). In conclusion, at energy balance exogenous ketone salts decreased respiratory exchange ratio without affecting glucose tolerance. NEW & NOTEWORTHY Our findings revealed that during isocaloric nutrition, additional exogenous ketone salts increased V̇o 2 and V̇co 2 while lowering the respiratory exchange ratio (RER). Ketone salts had no effect on postprandial glucose metabolism.